DANCE STUDIO MANAGEMENTRAFF DANCE COMPANY(RDC) IN SURABAYA CITY - Elvina Dewi Artanti; Trisakti (Jurnal Pendidikan Sendratasik, 2024)
This study aims to describe the dance learning management at the Raff Dance Company Surabaya Dance Studio, which includes planning, organizing, implementing, and supervising. The study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of the studio leader, trainers, administrators, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the dance learning management at the Raff Dance Company Dance Studio has been implemented quite well. Planning is carried out through the preparation of learning programs, dance materials, practice schedules, learning methods, and supporting activities that are adjusted to the age and abilities of students. Organization is carried out through a clear division of tasks within the studio's organizational structure. The implementation of learning is carried out routinely through dance practice activities, learning make-up and hair buns, creation of works, performances, certification, and the use of digital media as a means of promotion and documentation. Supervision is carried out directly by the leaders and trainers through learning evaluations, monitoring organizational activities, facilities and infrastructure, and performance evaluations. The implementation of these management functions supports the creation of a directed learning process and plays a role in the preservation and development of East Javanese dance arts.